The impact of local government restructuring on the functioning of the Kai !Garib Local Municipality - Du Plessis, Lyndon Mark (University of the Free State, 2005)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 The ultimate aim of government is to act on behalf of the citizens they serve. In doing so, governments have to render basic services and create an environment in which citizens can initiate endeavours to improve their living conditions. Government in South Africa was transformed in 1994 and the post 1994 government has since had the challenging task of providing services to citizens and eradicating the legacy of a previous system, characterised by disparities. / As far as direct responsibility for service rendering is concerned, local government has a particularly meaningful role, because it is the sphere of government people relate to most easily. In order to be able to meet the increasing challenges of governance, local government also underwent fundamental changes. 5 December 2000 heralded a new era for local government in South Africa, with the transformation of local government leading to the number of municipalities in the country being reduced from more than 800 to 284. These changes meant that many formerly independent municipalities have amalgamated to form new municipal organisations. Change in organisations invariably leads to conflict that, if not sufficiently dealt with can have a negative impact on the functioning of an organisation. The purpose of this study is to investigate the impact of local government restructuring on municipalities with specific reference to the Kai !Garib Local Municipality in the Northern Cape. The study focuses on aspects such as the historical development of local government in South Africa, the legislative framework for the new system of local government in the country as well as the need for efficient organisational structures as a means to deal with potential ill effects of the restructuring of local government. Finally, empirical research is conducted at the Kai ! Garib Local Municipality in order to determine the views of role players in the Municipality, and finding solutions to potential problem areas. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die uiteindelike doelwit van 'n regering is om namens die burgers wat dit dien op te tree. Om dit te doen moet regerings basiese dienste lewer en 'n omgewing skep waarbinne burgers inisiatiewe van stapel kan stuur om hul lewensomstandighede te verbeter. Die regering in Suid Afrika is in 1994 getransformeer en die post 1994 regering het sedertdien die uitdagende taak om dienste aan burgers the lewer en om die nalatenskap van 'n vorige bedeling wat / gekenmerk is deur ongelykhede uit te wis. In terme van direkte verantwoordelikheid vir dienslewering, het plaaslike regering 'n betekenisvolle rol, omdat dit die sfeer van regering verteenwoordig met wie mense die maklikste kan assosieer. Ten einde die toenemende uitdagings van regering na te kan kom, het plaaslike regering ook fundamentele veranderinge ondergaan. 5 Desember 2000 het 'n nuwe era vir plaaslike regering in Suid Afrika ingelui met hierdie transformasie wat gelei het tot die vermindering van die aantal munisipaliteite in die land van nagenoeg 800 tot 284. Hierdie veranderinge het in baie gevalle beteken dat voorheen onafhanklike munisipaliteite saamgevoeg is om nuwe munisipale organisasies te vorm. Verandering in organisasies lei dikwels tot konflik wat, indien dit nie aangespreek word nie, 'n negatiewe impak op die funksionering van 'n organisasie kan hê. Die doel van hierdie studie is om die impak van die herstrukturering van plaaslike regering op munisipaliteite te ondersoek met spesifieke verwysing na die Kai !Garib Plaaslike Munisipaliteit. Die studie fokus op aspekte soos die historiese ontwikkeling van plaaslike regering in Suid Afrika, die wetlike raamwerk vir die nuwe plaaslike regeringstelsel sowel as die belangrikheid daarvan om te midde van die herstrukturering doeltreffende organisatoriese strukture te vestig om moontlike negatiewe uitwerkings van herstrukturering die hoof te bied. Ten laaste is 'n empiriese ondersoek by die Kai !Garib Plaaslike Munisipaliteit onderneem om rolspelers by die munisipaliteit se mening rakende herstrukturering te bepaal en oplossings te vind vir potensiële probleemareas. ___________________________________________________________________
Dissertation (M.Pub. (Public Management))--University of the Free State, 2005
Keywords: Local government; Historical development; Restructuring; Transformation; Legislation; Organisational structures; Local government role players; Local government -- South Africa -- Northern Cape; Organizational change; Administrative agencies -- South Africa -- Norhern Cape -- gement